1999
DOI: 10.1144/jm.18.2.183
|View full text |Cite
|
Sign up to set email alerts
|

Marginal marine agglutinated foraminifera: affinities for mineral phases

Abstract: Abstract. The major agglutinated constituents in test material of marginal marine foraminifera are identified as α-quartz and clay particles using complementary spectroscopic techniques. Electron dispersive scattering analysis, micro-laser Raman and Fourier transform infrared (FTIR) spectroscopic techniques revealed detail about elemental and mineral polymorph constituents in test walls. Additionally, FTIR identifies the existence of organic cements and lining materials in wall structures. Micro-laser Raman sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…However, our results proved that although TOC content was high, this species occurred in the brackish water environment with high percentages of sand (up to 75%). Grain-size distribution, as well as the mineralogical composition of the sediment, has important implications for agglutinated taxa (ALLEN et al, 1999;ARMYNOT DU CHÂTELET et al, 2008;ARMYNOT DU CHÂTELET et al, 2013). SEM-EDS analysis showed that identified agglutinated foraminifera from the Marinska pond used variable mineral grains for building their tests (quartz, amphibole, mica and feldspars) (Fig.…”
Section: Foraminiferal Assemblages and Geochemical Characterization Omentioning
confidence: 99%
“…However, our results proved that although TOC content was high, this species occurred in the brackish water environment with high percentages of sand (up to 75%). Grain-size distribution, as well as the mineralogical composition of the sediment, has important implications for agglutinated taxa (ALLEN et al, 1999;ARMYNOT DU CHÂTELET et al, 2008;ARMYNOT DU CHÂTELET et al, 2013). SEM-EDS analysis showed that identified agglutinated foraminifera from the Marinska pond used variable mineral grains for building their tests (quartz, amphibole, mica and feldspars) (Fig.…”
Section: Foraminiferal Assemblages and Geochemical Characterization Omentioning
confidence: 99%
“…Other au thors ob served that some spe cies of ag glu ti nated foraminifera ex hibit clear af fin i ties to wards spe cific min eral phases, in volv ing a cu ri ous abil ity to dis tin guish be tween in divid ual min er als (e.g., Heron- Allen and Earland, 1912;Heron-Allen, 1915;Murray, 1971;Jorgensen, 1977;Allen et al, 1999;Laca et al, 2002;Kaminski et al, 2008). In case of the ma te rial ana lysed in the course of this study, tour ma line grains are con cen trated by se lected tax o nomic groups, namely Bathysiphon, Nothia, Psammosiphonella, Reophax, Recurvoides, Trochamminoides and Paratrochamminoides (Ap pendix 1).…”
Section: Discussionmentioning
confidence: 99%
“…The size of the grains seg re gated by spe cific spe cies is also pref er en tial (e.g., Heron-Allen, 1915;Smith and Kasler, 1970;Gooday nad Claugher, 1989;Allen et al, 1999;Bartholdy et al, 2005). Tour ma line grains typ i cal for flysch sed i ments rep re sent a rel a tively large build ing com po nent of the ana lysed tests , which is why their high est pro por tion oc curs in the coarse-grained tests of i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of grain type can seem relatively haphazard (Armynot du Châtelet et al, 2013) or it can be highly selective of both size and composition. Examples of selectivity include foraminifera that gather specific minerals, sometimes heavy ones, such as ilmenite (Makled and Langer, 2010), rutile (Cole and Valentine, 2006) and garnet (Allen et al, 1999), or particular biological clast types such as sponge spicules (Brady, 1879), echinoderm plates (Heron- Allen and Earland, 1909), or coccoliths (Holbourn and Kaminski, 1997;Thomsen and Rasmussen, 2008). It is also common for some agglutinated foraminifera to reuse the shells of dead planktonic foraminifera from the surrounding sediment in constructing their tubes (Brady, 1879;Cartwright et al, 1989).…”
Section: Introductionmentioning
confidence: 99%